Pengaruh Media Film Pendek tentang SADARI terhadap Pengetahuan dan Sikap pada WUS : (Studi di KUB Maria Assumpta Kelurahan Airnona Kota Kupang) - Modesta Yustina Yunita Goang; Ribka Limbu; Indriati A. Tedju Hinga (Yayasan Literasi Sains Indonesia, 2023)
Short films are one of the media in health education which has the advantage of being able to convey messages realistically, practically and flexibly. Breast self-examination (BSE) is very important to be used as health education using short films for women of childbearing age. The purpose of this study was to determine the effect of short film media about BSE on the knowledge and attitudes of women of childbearing age (WUS) at KUB Maria Assumpta, Airnona Village, Kupang City. This research is a quantitative research with a quasi-experimental design and uses a pre test-post test with control group design. This research was conducted at KUB Maria Assumpta, Airnona Village, Kupang City with a sample of 36 WUS, using total sampling. The data analysis used was univariate and bivariate analysis using the Paired T-Test statistic. The results showed that short film media had an effect on increasing knowledge and attitudes regarding BSE in WUS at KUB Maria Assumpta, Airnona Village, Kupang City with p value = 0.000 (p˂0.05). Researchers suggest that women of childbearing age learn more about BSE by choosing good health education media so that it is hoped that they can increase knowledge and attitudes about BSE.